The Ravens : The Ravens #1 - Morgan, Kass; Paige, Danielle (Novelist) (Boston ; New York : Houghton Mifflin Harcourt, 2021)
Loner Vivi Deveraux is thrilled to join Westerly College's Kappas, who are secretly witches, until she meets perfect, polished Scarlett Winter, who will stop at nothing to be the sorority's next president.
Ages 14 and up.
Grades 10-12.
Keywords: Witchcraft -- Fiction; Colleges and universities -- Fiction; Magic -- Fiction; Greek letter societies -- Fiction